Aspects of war in the late Middle Ages - Allmand, C. T., author.
1 online resource.
Keywords: "This Variorum collection of articles is intended to illustrate that conflict in the late Middle Ages was not only about soldiers and fighting (about the makers and the making of war), important as these were. Just as it remains in our own day, war was a subject which attracted writers (commentators, moralists and social critics among them), some of whom glorified war, while others did not. For the historian the written word is important evidence of how war, and those taking part in it, might be regarded by the wider society. One question was supremely important: what was the standing among their contemporaries of those who fought society's wars? How was war seen on the moral scale of the time? The last two sections deal with a particular war, the 'occupation' of northern France by the English between 1420 and 1450. The men who conquered the duchy, and then served to keep it under English control for those years, had to be rewarded with lands, titles, administrative and military responsibilities, even (for the clergy) ecclesiastical benefices. For these, war spelt 'opportunity', whose advantages they would be reluctant to surrender. The final irony lies in the fact that Frenchmen, returning to claim their ancestral rights once the English had been driven out, frequently found it difficult to unravel both the legal and the practical consequences of a war which had caused a considerable upheaval in Norman society over a period of a single generation"--